NATURAL RUBBER LOADED WITH LOCAL MATERIALS. III. CREEP PROPERTIES (Biological Sciences - PJSIR, 2003)
The creep properties (creep rate, creep modulus, creep compliance and tensile  creep) of natural  rubber  loaded  separately  with local clay, limestone, silica-sand and charcoal have been examined as a function of filler loading. filler  particle  size, stress level and temperature. Results reveal that creep rate  increases with  increasing  loading, stress level and temperature.  The clay loaded composites show lower creep rate and energy to resist deformation tha n for composites  loaded  with limestone, silica sand and charcoal. Clay therefore shows  a clear  advantage  over  limestone,  silica-sand  and  charcoal  in creep  deformation  resistance  when  used  as fillers  in  natural rubber.